Primordial cosmology - Peter, Patrick (Cadernos de Astronomia, 2023)
Primordial cosmology is concerned by the physics at the first moments of the Universe. It describes what is supposed to have happened to make predictions on the present-day observations, but it also can serve to extrapolate well-known theories to higher energies that are out of accelerator reach. Finally, it can be used as a testbed for quantum gravitation.